Coating properties of 1H,1H-perfluorooctylamine-terminated polyimides based on hexafluoroisopropylidene diphthalic anhydride and 1,4,5,8 naphthalenetetracarboxylic dianhydride - AKIN, EMRE; ÇAKIR, MUSTAFA; ARTIR, RECEP (SPRINGER, 2019)
This study attempted to prepare polyimide coatings (PIs) containing 6FDA (hexafluoroisopropylidene diphthalic anhydride) and/or NTDA (1,4,5,8 naphthalenetetracarboxylic dianhydride) in various ratios. 1% of these polyimide chains were terminated with 1H,1H-perfluorooctylamine (PFOA) and PFOA, and terminated polyimide coatings (PIFs) were prepared in the same ratios as PIs. Coatings were produced on aluminum substrates by a 75-mu m wire-wound applicator and thermally imidized. Finally, thermal, wear, and physical properties of PIFs and PIs were compared to each other. PIFs exhibited higher abrasion resistance than PIs due to the presence of PFOA. The increase in 6FDA content also resulted in elevated abrasion resistance. Both NTDA and 6FDA compounds improved thermal stability. The increase in NTDA content raised the T-g values of the polyimides. PIFs exhibited higher static water contact angle values than PIs, but the existence of microcracks decreased their hydrophobicity. The gloss values of PIFs were excellent. Improved values were obtained for pencil hardness, crosscut adhesion, and MEK (methyl ethyl ketone) rubbing properties for all coatings. In addition to the pencil hardness test, a pendulum hardness test was also carried out. The presence of PFOA affected pendulum hardness values positively, and the increase in the amount of 6FDA on polymer backbone improved the pendulum hardness values despite the rigidity of NTDA.
Keywords: Hydrophobic coatings; Thermal stability; Abrasion resistance; Polyimides; 1,4,5,8 naphthalenetetracarboxylic dianhydride; PHOSPHINE OXIDE; HYBRID COATINGS; FLUORINE; PERFORMANCE